Contact Allergy in Western Sweden to Propolis of Four Different Origins - Gunnar Nyman; Sara Oldberg Wagner; Katarzyna Prystupa-Chalkidis; Kristina Ryberg; Lina Hagvall (Medical Journals Sweden, 2020)
Propolis, which is produced by honeybees and is used in "natural" products, can cause contact allergy. The composition of propolis varies between regions, but little is known about how this variation affects contact allergenicity. The aims of this study were to investigate the frequency of propolis contact allergy in western Sweden, and whether the frequency varies according to the origin of the propolis. Patch-testing was performed using propolis from China, Lithuania, North America, and Sweden in 722 consecutive patients with dermatitis in western Sweden. Frequencies of positive patch-test reactions ranged from 2.4% to 3.6%. There were some, not statistically significant, differences in frequency of contact allergy to the 4 samples of propolis of different origins, with the highest frequency to the sample from China and the lowest frequency to the sample from Sweden. Concomitant positive patch-test reactions to plant and fragrance substances in the baseline series were common, most frequently to Myroxylon pereirae resin and colophonium.